Peran Ekstrak Daun Pepaya (Carica papaya Linn) terhadap Kematian Larva Nyamuk Aedes aegypti - Deby Swastika; Lenie Marlinae; laily khairiyati (Medical Laboratory Technology Journal, 2016)
Papaya plants contain many substances called papain, papain protease effect can kill larvae of Aedes aegypti. This study aimed to determine the effect of papaya leaves extracts (Carica papaya Linn) against Aedes aegypti larvae mortality. The research method was a quasi-experimental research design with Non-Equivalent Control Group. The concentration levels were 6.25%, 12.5%, 25%, 50%, 100%, and controls (CMC-Na) with 4 times replication. The Probit Analysis test results showed Lethal concentration (LC50) of papaya leaves extract (Carica papaya Linn) against Aedes aegypti larvae mortality was to 24.46% and the effective time is 22 hours. It is concluded that any different concentrations of papaya (Carica papaya Linn) leaves extract have effect on Aedes aegypti larvae mortality (p